Respuesta :

Answer:

x=3

Step-by-step explanation:

for 17.

we have that x=8 as one solution

then we have

x-8=0

so we know that

[tex]f(x)=(x-8)(something)[/tex]

[tex]\frac{f(x)}{x-8}=something[/tex]

so we divide and get that

[tex]something = x^{2} -6x+9x[/tex]

and we can factor it as

[tex](x-3)(x-3)[/tex]

so the other solutions are

x-3 =0

x = 3

this is a normal division

Ver imagen CSMedrano

Answer (#17):

(x-3) (x-3) or (x-3)²

Step-by-step explanation:

See attachment to find simplified equation. I can't explain synthetic division very well. Please find other sources to learn synthetic division or traditional algebraic long division.

Anyway, the image should be read first while this text explains the second part. Now you have the second equation, it can be factored down.

[tex]x^2-6x+9 = (x-3)(x-3)[/tex]

The function in factored form is : (x-3) (x-3)

Ver imagen imSolly
ACCESS MORE